Volleyball - Kluka, Darlene A.; Dunn, Peter J. (Boston : McGraw-Hill, 2000)
(NtOW^ HURAANGUJs
Includes bibliographical references (p. 195-196) and index.
Keywords: Volleyball -- history and special qualities